KHILAFIYAH DAN PERBEDAAN MAZHAB - St. Nurfadillah. A; A. Dwi Mulyana; Zubair; Andi Farras Abbiyu; M. Amin Umar (STKIP Subang, 2025)
Differences of opinion (khilafiyah) and the diversity of legal schools (madhhab) are inseparable realities within the Islamic intellectual tradition. These differences emerge from the dynamic process of ijtihad undertaken by Muslim scholars in interpreting and understanding the Qur’an and the Sunnah, particularly in matters of furū‘iyyah that lack definitive (qaṭ‘ī) textual evidence. This article aims to examine the concept of khilafiyah and the diversity of Islamic legal schools, as well as to analyze Muhammadiyah’s perspective in responding to these phenomena. This study employs a qualitative method with a library research approach by examining classical fiqh literature, scholarly works, and official Muhammadiyah documents. The findings indicate that khilafiyah and differences among legal schools represent a form of Islamic intellectual richness, reflecting the flexibility and comprehensiveness of Islamic law. Muhammadiyah views these differences as an inevitable reality that should be managed in a scholarly, moderate, and tolerant manner through a return to the Qur’an and the Sunnah, the application of manhaj tarjīḥ, collective ijtihad (ijtihād jamā‘ī), and the rejection of excessive madhhab fanaticism. Through this approach, khilafiyah is not a source of conflict but a means of strengthening Islamic brotherhood and advancing progressive Islamic thought. This study is expected to contribute theoretically to a more proportional understanding of madhhab differences and to promote inclusive and constructive religious attitudes amid the plurality of the Muslim community. Keywords: Khilafiyah, Madhhab Differences, Islamic Jurisprudence, Ijtihad, Muhammadiyah